Subjective and physiological measures of well-being: an exploratory analysis using birth-cohort data - Daniela Andrén; Andrew E. Clark; Conchita D'Ambrosio; Sune Karlsson; Nicklas Pettersson (Örebro University School of Business, 2017)
We use a rich longitudinal data set following a cohort of Swedish women from age 10 to 49 to analyse the effects of birth and early-life conditions on adulthood outcomes. These latter include both well-being and the stress hormone cortisol. Employment and marital status are important adult determinants of well-being. Log family income and absence from school also predict adult well-being, although their importance falls when controlling for adult and birth characteristics. Among the birth characteristics, we find that high birth weight (>4.3kg) affects adult well-being. We predict the level of adult cortisol only poorly, and suggest that the relationship between life satisfaction and cortisol is non-monotonic: both high and low cortisol are negatively correlated with life satisfaction. The results from an OLS life satisfaction regression and a multinomial logit of high or low cortisol (as compared to medium) are more similar to each other.
Keywords: A12; D60; I31; 330; life satisfaction; cortisol; birth-cohort data; adult; child and birth outcomes; multivariate imputation by chained equations